Elementary school students’ conceptualizations of bullying, role-based emotions, and coping strategies: a thematic analysis - Ade Nursanti; Entin Nurhayati (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2026)
Bullying is a form of violence that has significant impacts. This study investigates primary school students’ conceptualizations of bullying, based on role-based emotions and coping strategies. Previous research has shown that bullying also occurs in elementary schools, but few have tried to explore the emotions and coping strategies that may be used by elementary school students.  This study employed a qualitative descriptive design using written interviews. In this study, 88 male elementary school students participated. The data were analyzed manually using thematic analysis, guided by the Consolidated Criteria for Reporting Qualitative Research (COREQ) checklist. The results show that four main themes and 15 subthemes were identified as perceived by students: Definition of bullying, Types of bullying, Participants’ perceived emotions by role, and Participants’ perceived coping strategies employed. The findings indicate that bullying occurs in various forms and has negative impacts on perpetrators, victims, and bystanders. The uniqueness in this study was one of the effects of the perpetrator, namely the feeling of pleasure and satisfaction as a perpetrator.  Meanwhile, students perceived strategies for addressing bullying include reporting incidents to teachers or other adults, avoiding perpetrators, assisting victims, and, in some cases, expressing a desire for retaliation. The implications of this study highlight that preventing bullying can start from the school environment by building a positive relationship between teachers and students, creating a supportive classroom climate and providing a safe and comfortable environment for students, and teaching students to strengthen emotional regulation and empathy.